Phase I Cardiac Rehabilitation Intervention In Patients Undergoing Coronary Artery Bypass Grafting - Ardhani Galih; Cholid Tri Tjahjono; Ardian Rizal; Heny Martini (Heart Science Journal, 2022)
Patients undergoing coronary artery bypass grafting (CABG) have a risk of postoperative complications that result in prolonged hospitalization and even death. Interventions in the form of phase I cardiac rehabilitation are needed to help speed up the postoperative recovery process and prevent complications after CABG. Although a lot of research has been carried out, it is necessary to conduct further studies of research articles regarding interventions that can be carried out in cardiac rehabilitation programs that are safe and easy to perform in postoperative CABG patients. The purpose of this literature review was to examine safe and effective interventions in phase I cardiac rehabilitation in patients undergoing CABG. The implementation of phase I cardiac rehabilitation in patients undergoing CABG started from the preoperative phase and continued postoperatively until the patient was discharged. Phase I cardiac rehabilitation interventions, both pre and postoperative, consist of education and counselling, physical exercise, breathing exercises, effective coughing exercises, inspiratory muscle training, and chest physiotherapy. The results of this literature review can be used as a basis for determining standard operating procedures for the implementation of phase I cardiac rehabilitation for hospitals that provide CABG services.